A phenomenological exploration of self-identified origins and experiences of body dysmorphic disorder - Craythorne, Shioma-Lei; Shaw, Rachel L.; Larkin, Michael (Frontiers in Psychology, 2022)
Body dysmorphic disorder (BDD) is a debilitating mental health condition that presently affects approximately 2% of the general population. Individuals with BDD experience distressing preoccupations regarding one or more perceived defects in their physical appearance. These preoccupations and perceived distortions can have profound impact on key areas of social functioning and psychological health. Individuals’ BDD origins have not been explored in significant depth and have been, often unhelpfully, conflated with social media usage and exposure to idealistic imagery of the body. Such generalisations fail to acknowledge the complexity of BDD development and onset, highlighting the importance of moving towards an understanding of people’s implicit theories regarding their own experience. It is therefore essential to gain insight into how individuals make sense of the experiences which they believe led to the development and onset of BDD. The aim of this exploratory study was to elicit and phenomenologically analyse the accounts of individuals with lived experience of BDD in order to examine their beliefs about its origins and understand how they navigate the world with a distorted sense of self. Participants provided written and verbal accounts regarding both their BDD onset and experiences of living with the disorder. Both components of the study were analysed using interpretative phenomenological analysis. Four main themes were generated from the data: Exposure to bullying and external critique of appearance; Experiencing rejection, shame, and a sense of not being enough; Developing an awareness of the solidification of concerns, and Learning about and reflecting upon triggers. Participants attributed their BDD onset to adverse experiences such as childhood bullying, receiving appearance-focused criticism, rejection, and being subjected to emotional and physical abuse. The findings from this study highlight the complexity of BDD development and onset in individuals, and the need for appropriate care and treatment for those affected by BDD.